DNA Cloning and Assembly Methods - Valla, Svein; Lale, Rahmi; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2014)
In DNA Cloning and Assembly Methods, expert researchers in the field detail many of the methods which are now commonly used for DNA cloning and make cloning procedures faster, more reliable and also suitable for high-throughput handling. These include methods and protocols that are based on several mechanisms including type II and IIS restriction enzymes, single stranded annealing, sequence overlap, and recombination. With additional chapters on software programs that are suitable for primer design, a feature crucial for the functionality of the described methods. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, DNA Cloning and Assembly Methods seeks to provide  scientist with a valuable and useful resource for wet lab researchers within life sciences.
BioBrick Assembly Standards and Techniques and Associated Software Tools -- Plasmid Construction by SLIC or Sequence and Ligation Independent Cloning -- Quick and Clean Cloning -- Hierarchical Ligation-Independent Assembly of PCR Fragments -- USER-Derived Cloning Methods and Their Primer Design -- Application of the Restriction-Free (RF) Cloning for Multi-Components Assembly -- A Single-Tube Assembly of DNA Using the Transfer-PCR (TPCR) Platform -- Circular Polymerase Extension Cloning -- Golden Gate Cloning -- Design and Construction of Multigenic Constructs for Plant Biotechnology Using the GoldenBraid Cloning Strategy -- FX cloning: A Simple and Robust High-Throughput Cloning Method for Protein Expression -- Minimum GC-rich Sequences for Overlap Extension PCR and Primer Annealing -- Simple Cloning and DNA Assembly in Escherichia coli by Prolonged Overlap Extension PCR -- Combinatorial Assembly of Clone Libraries Using Site-Specific Recombination -- Application of In-Fusion™ Cloning for the Parallel Construction of Escherichia coli Expression Vectors -- SeamLess Ligation Cloning Extract（SLiCE）Cloning Method -- j5 DNA Assembly Design Automation -- FASTPCR Software for PCR, in silico PCR, and Oligonucleotide Assembly and Analysis.
Keywords: Human genetics; Medical genetics; Human Genetics; Gene Function